2008
DOI: 10.1093/jb/mvn055
|View full text |Cite
|
Sign up to set email alerts
|

Elongation and Desaturation of Fatty Acids are Critical in Growth, Lipid Metabolism and Ontogeny of Caenorhabditis elegans

Abstract: Recently, it was reported that a deficit in the mouse stearoyl-CoA desaturase 1 gene decreases biosynthesis and accumulation of fatty acid and revitalizes the beta-oxidation of fatty acid. To examine the physiological role of fatty acid desaturase (FAT) and elongase (ELO)-gene transduction in ontogeny, fatty acid accumulation and individual lifespan, we performed bacteria-mediated RNA interference (RNAi) in the nematode Caenorhabditis elegans. Suppression of the expression of FAT-2 gene mRNA caused a drastic d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 41 publications
5
29
0
Order By: Relevance
“…In the same way, b-oxidization was induced and weight was not changed by feeding the high fat food in mouse that lacked D9 stearoyl-CoA desaturase (SCD-1) (Dobrzyn et al 2005). It has been reported that the fat-7 expression decreases in sbp-1 knockdown worms and that egg-laying activity is reduced in sbp-1 knockdown worms [33,38]. Our observations correspond with these findings.…”
Section: Sbp-1 Regulates the Phenotype Of C Eleganssupporting
confidence: 92%
See 1 more Smart Citation
“…In the same way, b-oxidization was induced and weight was not changed by feeding the high fat food in mouse that lacked D9 stearoyl-CoA desaturase (SCD-1) (Dobrzyn et al 2005). It has been reported that the fat-7 expression decreases in sbp-1 knockdown worms and that egg-laying activity is reduced in sbp-1 knockdown worms [33,38]. Our observations correspond with these findings.…”
Section: Sbp-1 Regulates the Phenotype Of C Eleganssupporting
confidence: 92%
“…Caenorhabditis elegans produces three D9 desaturases (fat-5, fat-6, and fat-7), as well as D3, D5, D6, and D12 desaturases; thus, it can produce multiple kinds of fatty acids [34][35][36][37][38]. By contrast, mammals lack D3 and D12 desaturases, which prevents them from producing polyunsaturated fatty acids (PUFAs) endogenously and makes it necessary for them to obtain PUFAs from food.…”
Section: Introductionmentioning
confidence: 99%
“…After 72 hrs culture, worms were collected, treated with 0.2% PFA solution, and observed under a fluorescence microscope (DMRXA, Leica) with N3 filter (565 nm, Leica) (Ashrafi et al 2003;Horikawa et al, 2008).…”
Section: Nile Red Assaysmentioning
confidence: 99%
“…Simultaneously, the addition of the herbal extracts reduced fat accumulation in a dose-dependent manner [ Figure 1]. Nile red staining is the standard method for lipid detection in nematodes, [1] but it does not exclusively detect neutral lipids. Therefore, it is not clear whether the herbal extracts affected lipid synthesis, accumulation, or digestion.…”
Section: Discussionmentioning
confidence: 99%
“…C. elegans has been frequently used as a human model organism because its whole genome has been determined, various genetic mutants are available, and many genetic manipulation techniques, such as gene transfer, are established. [1,2] Furthermore, it is easy to culture, and it is also possible to ensure substance intake by culturing with Escherichia coli as feed and using culture media mixed with certain external reagents. We have used C. elegans as a model animal for the assessment of bioactivity of phytochemicals and other agents.…”
Section: Introductionmentioning
confidence: 99%